Educator Recruitment and Selection Strategies in Private Universities in Indonesia: Policies and Practices - Farida Suldina Achmad; Ika Widiastuti (STAI Hubbulwathan Duri, 2024)
The recruitment and selection of educators play a pivotal role in enhancing the quality of higher education in Indonesian private universities. Understanding the strategies and policies involved in this process is vital to improving institutional outcomes. This study conducts a Systematic Literature Review (SLR) of 25 peer-reviewed articles published between 2013 and 2023, focusing on educator recruitment and selection strategies in Indonesian private universities.. Using the Systematic Literature Review (SLR) method, relevant articles were gathered from databases including Google Scholar, PubMed, Scopus, and ERIC. The search utilized keywords such as educator recruitment, selection strategies, private universities, and higher education employment policies. The analysis involved thematic synthesis, identifying trends, challenges, and best practices within the literature. The findings reveal that private universities prioritize educator qualifications, alignment with institutional values, and cultural fit during recruitment. However, they face challenges such as attracting highly qualified educators due to competitive job markets. Moreover, the literature lacks sufficient exploration of digital recruitment tools and their long-term impact on educational quality, indicating an area for future research. This review suggests that future research should explore innovative recruitment strategies, including integrating digital tools, to improve recruitment outcomes and enhance educational quality in private universities.